Effectiveness of Consumer Dispute Resolution through the Consumer Dispute Resolution Agency (BPSK) - M. Sunandar Yuwono; Faisal Santiago (Yayasan Adra Karima Hubbi, 2024)
Background. Consumer protection is an essential aspect of fair business practices. In Indonesia, the Consumer Dispute Resolution Agency (BPSK) was established to provide an alternative to formal courts for resolving consumer disputes. However, issues such as legal loopholes, limited resources, and low public awareness challenge its effectiveness. Purpose. This study evaluates the effectiveness of BPSK in resolving consumer disputes and protecting consumers from harmful business practices. Method. A normative legal method was applied, focusing on the legal norms in Law Number 8 of 1999 concerning Consumer Protection (UUPK). Data were collected through document studies, including legal literature, academic journals, official reports, and regulatory frameworks. Findings. The study reveals that BPSK offers faster and more efficient dispute resolution compared to formal courts. However, challenges such as objection procedures against decisions, limited human resources and budget, and inadequate public knowledge of consumer rights hinder its optimal functioning. Conclusion. To improve BPSK’s effectiveness, its legal position must be strengthened, resources enhanced, and regulations refined. Additionally, public awareness campaigns are essential to ensure wider utilization of BPSK services. These measures aim to achieve legal certainty and justice for consumers in Indonesia.